Ч . 3 : Введение в процесс бурения; Нефтегазовое дело. Книга для студентов - Болсуновская Л. М. Людмила Михайловна; Коротченко Т. В. Татьяна Валериевна; Ульянова О. С. Оксана Сергеевна; Зеремская Ю. А. Юлия Александровна (2015, 2015)
Заглавие с титульного экрана